2013
DOI: 10.1097/prs.0b013e3182a48b10
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Five Alternative Methods of Breast Reconstruction Surgery

Abstract: Autologous pedicled tissue was slightly more cost-effective than free tissue reconstruction in irradiated and nonirradiated patients. Implant-based techniques were not cost-effective. This is in agreement with the growing trend at academic institutions to encourage autologous tissue reconstruction because of its natural recreation of the breast contour, suppleness, and resiliency in the setting of irradiated recipient beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 53 publications
1
37
0
4
Order By: Relevance
“…Although results of the current study are in agreement with previous research that demonstrates the cost effectiveness of autologous reconstruction, the BREAST-Q has enabled use of an effectiveness measure derived from patients, creating a more robust cost-effectiveness model. 14,15 Immediate autologous reconstruction rates in the United States have remained unchanged, whereas there has been a dramatic increase in prosthesis-based techniques. 1 Reimbursement has been identified as a barrier preventing plastic surgeons from offering autologous reconstruction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although results of the current study are in agreement with previous research that demonstrates the cost effectiveness of autologous reconstruction, the BREAST-Q has enabled use of an effectiveness measure derived from patients, creating a more robust cost-effectiveness model. 14,15 Immediate autologous reconstruction rates in the United States have remained unchanged, whereas there has been a dramatic increase in prosthesis-based techniques. 1 Reimbursement has been identified as a barrier preventing plastic surgeons from offering autologous reconstruction.…”
Section: Discussionmentioning
confidence: 97%
“…In breast reconstruction, the only cost-effectiveness analysis that compares autologous tissue to implants generated utilities derived from plastic surgeons without patient input. 14 With development of the BREAST-Q, the impact of breast reconstruction on health-related quality of life and patient satisfaction can now be measured from people who have the condition under study. 14,15 A cost-effectiveness analysis of these two reconstructive methods that includes cost and an effectiveness measure derived from patients (BREAST-Q) will be important to both payers and health policy makers.…”
mentioning
confidence: 99%
“…This provides a more realistic quality of life assessment than utilities derived from surveys of plastic surgeons or healthy volunteers. 30 Limitations are inherent to any CEA where certain assumptions need to be made for model creation. For example, these include but are not limited to only one complication per person, lifespan of 7 years following diagnosis, and variations in BREAST-Q scores.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cost‐effective analysis by Grover et al showed that autologous tissue transfers are the most cost‐effective and should be encouraged to be performed in higher numbers at academic institutions and for training purposes.…”
Section: Clinical and Demographic Detailsmentioning
confidence: 99%